Comparative Study of PJBL-STEM Learning Models: Analyzing Similarities and Differences Between Two Research Articles - Kussudarto, Ratna Eka Anggareni; Rosdiana, Laily (Science Education and Application Journal, 2024)
A Comparative Study of PJBL-STEM Learning Models: Analyzing Similarities and Differences Between Two Research Articles. This study aimed to compare two research studies that focused on the implementation of Project-Based Learning (PjBL) integrated with STEM in enhancing students' critical thinking, conceptual understanding, and creativity. The research employed a qualitative methodology, specifically content analysis, with data gathered through a literature review. Articles were selected based on specific criteria, including the accreditation ranking of the publishing journal, relevance to the topic, and citation impact. Data was collected using Google Scholar and Publish or Perish with keywords such as “Project-Based Learning” and “STEM.”. The findings reveal key similarities between the studies, notably the success of PjBL-STEM in improving students' scientific skills. However, the studies differ in their research objectives, target subjects, methodologies, and data collection instruments, highlighting varied focuses and anticipated outcomes. For instance, one study may prioritize critical thinking while another emphasizes conceptual understanding. The study concludes that integrating PjBL with STEM significantly enhances students' critical thinking, conceptual grasp, and creative problem-solving abilities. These findings demonstrate that PjBL-STEM is an effective and comprehensive educational strategy, preparing students to meet real-world challenges by developing essential scientific and creative skills.